Analisis Kelayakan Bisnis pada Toserba Saudi Pemalang Cabang Ulujami Ditinjau Dari Aspek Pasar dan Pemasaran - Khotimah, Lala Ratu; Abadi, Muhammad Taufiq (CV. Kalimasada Group, 2023)
Doing business can be an opportunity to get a better life and business activities can be carried out by anyone who intends to do it. To be able to survive entering the business world, an entrepreneur needs to carry out a business feasibility study to measure the sustainability of the business in the long term. Studying the feasibility of this business is very useful for business people in seeing estimates of how their business will change in the future. The data analysis method used is a qualitative analysis of the Business Feasibility Study in terms of market and marketing aspects, the setting of this research is located at the Ulujami branch of the Saudi Department Store, Pemalang district. The purpose of this study is that researchers can broadly determine the feasibility of existing businesses at the Ulujami branch of the Saudi Department Store in terms of market and marketing aspects. The results and discussion include the 4Ps namely Product, Price, Place, and Promotion. As well as the conclusion that the Ulujami branch of the Saudi Department Store is feasible when viewed from the market and marketing aspects.